Assessment of passengers 'satisfaction from the organization of MPK Kraków public transport services - Brożyna, Ewa (AUTOBUSY – Technika, Eksploatacja, Systemy Transportowe, 2018)
This article raises a subject of organization quality of public transport services. The author presented in it the results of the second part of the original research conducted among passengers of Miejskie Przedsiębiorstwo Komunikacyjne S.A. in Krakow, which showed the level of passenger satisfaction from the three aspects of the transport organization of MPK Kraków, which are: accessibility of the communication network (availability of connections and deployment of stops), information system (information channels for passengers and the level of culture and competence in servicing passengers) and issues related to tickets (operation of ticket machines, operation of the Krakowska Karta Miejska, ticket control). The aim of the research was to acquire knowledge about the passengers' perception of the quality in organization of MPK Krakow services and to develop on this basis practical tips and suggestions regarding the directions of actions that can be taken to improve the organization of these services.